Breaking the Rules: An Analysis of Flouting Maxim in "Joker" (2019) - Tunliu, Dian; Agustin, Laila Winda; Noor, Syamsiah; Permana, Helmy Septian; Nike Dwi Adisty; Suhayati, Lisa (Global Expert: Jurnal Bahasa dan Sastra, 2025)
This study examines the flouting of conversational maxims in the film Joker (2019) using Grice’s Cooperative Principle. Pragmatics highlights that speakers do not always communicate meaning directly, and maxim flouting becomes a strategy to express hidden intentions, emotional states, or social criticism. Although several studies have explored maxim flouting in various films, limited research focuses on how linguistic flouting in Joker reflects psychological instability and social conflict. This research uses a mixed-method descriptive qualitative method by analyzing selected utterances from the Joker transcript that demonstrate deliberate flouting of the Maxims of Quantity, Quality, Relation, and Manner. Each utterance was examined based on context and the type of maxim flouted to uncover its pragmatic implications. The findings show that the Maxim of Relation is the most frequently flouted (43.5%), followed by Quantity (22.6%), Quality (19.4%), and Manner (14.5%). These patterns indicate that characters often respond irrelevantly or shift topics, suggesting avoidance, emotional distancing, or attempts to challenge social norms. The maxim flouting reflects Arthur’s psychological tension, expresses sarcasm or concealed messages, highlights power relations between characters, and strengthens the film’s social critique. By violating expected conversational norms, Arthur and other characters communicate meanings that cannot be expressed directly, such as frustration, resistance, or emotional pain. In conclusion, flouting maxims in Joker functions as a narrative device that conveys character development and thematic depth. The study contributes to pragmatic research by showing how linguistic strategies in film dialogue reveal complex psychological and social dimensions. Keywords: Flouting Maxim, Maxim, Linguistics, Joker (2019), Pragmatics